Impact of fatty acid binding protein 5‐deficiency on COPD exacerbations and cigarette smoke‐induced inflammatory response to bacterial infection. Issue 1 (15th March 2019) - Rao, Deviyani M.; Phan, Della T.; Choo, Michelle J.; Weaver, Michael R.; Oberley‐Deegan, Rebecca E.; Bowler, Russell P.; Gally, Fabienne
Abstract: Background: Although cigarette smoking (CS) is by far the most important risk factor of chronic obstructive pulmonary disease (COPD), repeated and sustained infections are clearly linked to disease pathogenesis and are responsible for acute inflammatory flares (i.e. COPD exacerbations). We have previously identified Fatty Acid Binding Protein 5 (FABP5) as an important anti‐inflammatory protein in primary airway epithelial cells. Results: In this study we found decreased FABP5 mRNA and protein levels in peripheral blood mononuclear cells (PBMCs) of COPD patients, especially among those who reported episodes of COPD exacerbations. Using wildtype (WT) and FABP5 −/− mice, we examined the effects of FABP5 on CS and infection‐induced inflammatory responses. Similarly to what we saw in airway epithelial cells, infection increased FABP5 expression while CS decreased FABP5 expression in mouse lung tissues. CS‐exposed and P. aeruginosa ‐infected FABP5 −/− mice had significantly increased inflammation as shown by increased lung histopathological score, cell infiltration and inflammatory cytokine levels. Restoration of FABP5 in alveolar macrophages using a lentiviral approach attenuated the CS‐ and bacteria‐induced pulmonary inflammation. And finally, while P. aeruginosa infection increased PPARγ activity, CS or FABP5 knockdown greatly reduced PPARγ activity. Conclusions: These findings support a model in which CS‐induced FABP5 inhibition contributes to increased inflammation in COPD exacerbations. It is interesting to speculate that the increased inflammation is a result of decreased PPARγ activity.